2019
DOI: 10.1093/ehjqcco/qcy062
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal and soft tissue injuries after manual and mechanical chest compressions

Abstract: Aims To determine the rate of injuries related to cardiopulmonary resuscitation (CPR) in cardiac arrest non-survivors, comparing manual CPR with CPR performed using the Lund University Cardiac Assist System (LUCAS). Methods and results We prospectively evaluated 414 deceased adult patients using focused, standardized post-mortem investigation in years 2005 through 2013. Skeletal and soft tissue injuries were noted, and soft t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 35 publications
0
12
0
2
Order By: Relevance
“…The only randomised trial of devicerelated injuries so far did not include the Corpuls CPRdevice used in this study, but the piston-based device analysed in that study, LUCAS, was found to be noninferior to manual CPR in terms of severe injuries [17]. By contrast, in two other recently published large studies, patients resuscitated with the LUCAS-device had more resuscitation-related injuries [18,19], even though this effect lost statistical significance after adjusting for CPRduration in one of the studies [18]. In case of evacuation from an upper floor, we would still suggest using CPRdevices, even if their injury potential were higher, because of the improvement of CPR-quality versus manual CPR, which performs poorly in this situation.…”
Section: Discussionmentioning
confidence: 85%
“…The only randomised trial of devicerelated injuries so far did not include the Corpuls CPRdevice used in this study, but the piston-based device analysed in that study, LUCAS, was found to be noninferior to manual CPR in terms of severe injuries [17]. By contrast, in two other recently published large studies, patients resuscitated with the LUCAS-device had more resuscitation-related injuries [18,19], even though this effect lost statistical significance after adjusting for CPRduration in one of the studies [18]. In case of evacuation from an upper floor, we would still suggest using CPRdevices, even if their injury potential were higher, because of the improvement of CPR-quality versus manual CPR, which performs poorly in this situation.…”
Section: Discussionmentioning
confidence: 85%
“…There are also concerns regarding potential injuries from the more powerful compressions delivered. Observational studies found that LUCAS CPR resulted in a higher incidence of skeletal and soft tissue injury than manual CPR ( 9 , 10 ). Conversely, a recent randomized controlled trial did not find that the LUCAS caused any more serious or life-threatening visceral damage than manual CPR did ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…In an animal model, the LUCAS™ device shows superior resuscitation outcomes and less thoracic injuries, compared to the Corpuls CPR [ 63 ]. However, in forensic autopsy studies, the use of LUCAS™ compared with manual CPR was associated in part with significantly higher rates of sternal fractures, rib fractures, and severe soft tissue injuries, including several case reports of potentially life-threatening injuries [ 64 , 65 , 66 , 67 ]. In comparison, the patterns of trauma in autopsy records between AutoPulse ® CPR and manual CPR showed different characteristic patterns of injuries.…”
Section: Introductionmentioning
confidence: 99%